KAJIAN SIFAT FISIKA TANAH BEBERAPA PENGGUNAAN LAHAN DI BUKIT GAJABUIH KAWASAN HUTAN HUJAN TROPIK GUNUNG GADUT PADANG - Yulnafatmawita Yulnafatmawita; Utri Luki; Afri Yana (Jurnal Solum, 2007)
Study about soil physical properties of Bukik Gajabuih Padang, the area receiving high annual rainfall (>5000 mm), was conducted at different land uses in 2006.  The objective of this research was to measure the change of soil physical properties as forest was cut down and converted into mixed perennial plant field and into bush land.  The results showed that changing forest area into land use for mixed perennial trees for more than 50 years increased SOM content on the top 0-20 cm, but decreased on the 20-40 cm layer.  The highest SOM content was found under bush land.  Therefore, the bulk densisty of the soil decreased from forest to mixed land use and to bush land. The opposite trend was found for total pores and permeability rate.  While the plasticity index of the soil followed the clay percentage of the soil texture, it increased by increasing clay content of soil from forest into mixed field and bush land use.Key Words: Land Use Change, Soil Organic Carbon, Soil Physical Properties